2016
DOI: 10.2147/ndt.s59271
|View full text |Cite
|
Sign up to set email alerts
|

Optimal management of ADHD in older adults

Abstract: BackgroundThe manifestation of attention-deficit/hyperactivity disorder (ADHD) among older adults has become an interesting topic of interest due to an increasing number of adults aged 50 years and older (≥50 years) seeking assessment for ADHD. Unfortunately, there is a lack of research on ADHD in older adults, and until recently only a few case reports existed.MethodA systematic search was conducted in the databases Medline/PubMed and PsycINFO in order to identify studies regarding ADHD in adults ≥50 years.Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 95 publications
0
39
0
4
Order By: Relevance
“…In older adults with ADHD, no randomized controlled trials (RCTs) have been performed so far to examine the effect and safety of stimulants; more information is available on treatment of older patients with methylphenidate in depression and dementia (see paragraphs below) [83]. However, case studies show beneficial effects of stimulants in this age group.…”
Section: Methylphenidatementioning
confidence: 99%
“…In older adults with ADHD, no randomized controlled trials (RCTs) have been performed so far to examine the effect and safety of stimulants; more information is available on treatment of older patients with methylphenidate in depression and dementia (see paragraphs below) [83]. However, case studies show beneficial effects of stimulants in this age group.…”
Section: Methylphenidatementioning
confidence: 99%
“…Adult ADHD can be found in the research literature since 1976 (Wood, Reimherr, Wender, & Johnson, 1976). Subsequent research shows that ADHD persists into adulthood (Fayyad et al, 2017;Semeijn et al, 2016), and old age (Torgersen, Gjervan, Lensing, & Rasmussen, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A growing number of people age 50 years and older are diagnosed and treated for ADHD worldwide (Torgersen et al, 2016). In Longitudinal Aging Study Amsterdam (LASA), Michielsen et al (2012) by a random sample of men and women (N ¼ 231) aged 55-85 years, concluded that 2.8% of older adults had full-blown syndromatic ADHD and 4.2% symptomatic ADHD.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological treatment in older adults should generally follow similar guidelines as with younger patients except that drug dosing and speed of titration should be slower and start lower. Side effect profile is a greater consideration than with younger patients (5). Research on ADHD is proceeding exponentially.…”
Section: Perspectivesmentioning
confidence: 99%
“…ADHD afflicts 7-8% of school-age children and 4-5% of the adult population (2,3). In fact, while some "outgrow" the disorder, symptoms persist beyond adolescence in as many as 65% of individuals (4,5).…”
Section: Introductionmentioning
confidence: 99%